The role of eddies for the deep water formation in the Labrador Sea - Czeschel, Lars (2004)
Previous ocean general circulation models of the North Atlantic tend to show large deficits in simulating observed characteristics of deep water formation in the Labrador Sea. It is shown that three key processes lead to significant improvements: 1) an adequate representation of the freshwater exchange with the Nordic Seas; 2) an efficient representation of eddy fluxes between the boundary currents and the interior of the Labrador Sea; 3) low (numerical) diapycnal mixing. Based on these results, a refined eddy resolving model of the North Atlantic is developed and analyzed. The model suggests two novel mechanisms of convection variability related to wind stress: 1) in case of enhanced wind stress a higher generation of well stratified Cape Desolation eddies leads to significantly lower Labrador Sea Water formation; 2) wind stresses parallel to the coast west of Greenland causes Ekman transports of relatively fresh and cold water off the coast towards the interior. This buoyant water at the surface stratifies the water column on the Greenland side of the Labrador Sea and suppresses deep convection.